Snowblind - Ragnar Jónasson, 1976- (Ragnar Jónasson, 1976- Dark Iceland series., 2017)
"Siglufjörður: an idyllically quiet fishing village in Northern Iceland, where no one locks their doors -- accessible only via a small mountain tunnel. Ari Thór Arason: a rookie policeman on his first posting, far from his girlfriend in Reykjavik--with a past that he's unable to leave behind. When a young woman is found lying half-naked in the snow, bleeding and unconscious, and a highly esteemed, elderly writer falls to his death in the local theater, Ari is dragged straight into the heart of a community where he can trust no one, and secrets and lies are a way of life. Past plays tag with the present and the claustrophobic tension mounts, while Ari is thrust ever deeper into his own darkness -- blinded by snow, and with a killer on the loose. Taut and terrifying, Snowblind is a startling debut from an extraordinary new talent. "--